Characteristics of Milkfish Sausage (Chanos chanos) and Carrots (Study of Proportions of Tapioca Flour: Taro Starch and Addition of Egg White) - Hakim Putra Ashari; Rosida .; Anugerah Dany Priyanto (JITIPARI, 2023)
The purpose of this research was to study the manufacture of milkfish and carrot sausages by treating the proportion of tapioca flour: taro starch and the addition of egg white on physicochemical and organoleptic properties. The use of taro starch is because contains amylose and amylopectin which can bind air more strongly and can make the texture more springy. Carrots are used for coloring sausages because they contain carotenoid compounds. Egg whites are used to increase protein levels. This study used a completely randomized design with two factors, namely the proportion of tapioca flour to taro starch (75:25; 50:50; 25:75) and the addition of egg white (3, 6, 9%). The results showed that the proportion of tapioca flour: taro starch and the addition of egg white had a significant effect on moisture and ash content. However, it did not significantly affect the levels of fat, protein, starch, emulsion stability, and hardness. The best treatment was obtained from the combination of the dimensions of the proportion of tapioca flour: taro starch (25: 75) and the addition of 9% egg white which obtained a moisture content of 72.69%; ash 2.45%; fat 2.31%; protein 12.16%; starch 7.14%; emulsion stability 99.06%; hardness 2.59 kg.m/s2; and hedonic color 3.76 (neutral); fragrance 4.00 (like); taste 4.28 (like); and texture 4.48 (like).